Hyperspectral sensing of acid sulphate soils and their environmental impacts in South Yunderup, Western Australia - Shi, Xianzhong (Curtin University, 2014)
Several sources of hyperspectral data were used to map the occurrence and spread of acid sulfate soils (AAS). Surface evolution of mineralogy during controlled oxidation of sulphidic material showed the formation of secondary iron minerals linked to soil pH ranges. Spectral characterization, image classification and PLSR of hyperspectral data successfully mapped the occurrence of surface and subsurface acid conditions and related toxicity by linking mineralogy to pH.